UPAYA MELESTARIKAN BAHASA DAERAH BEBASAN (JAWA SERANG) MELALUI KONTEN DIGITAL - Muhammad Frandy Ramadinatha; Iik Dwi Aldi; Mira Marlina (Indonesian Collaboration Journal of Community Services, 2021)
Along with the development of the times and the rapid flow of information, regional languages ??began to be eroded by other languages ??that were considered more modern. The people of Banten themselves are starting to be reluctant to use their own regional language in their daily life, one of which is the Javanese language of Serang smooth/Bebasan. If this continues, it could be that the regional language will only become history. This Banten Javanese language is spoken in several areas such as the north of Serang Regency, Serang City, Cilegon City and the western area of ??Tangerang Regency. The younger generation is expected to be the successor and inheritor of the regional cultural wealth, including language. The development of information technology today can be used as a channel of information easily to the public anywhere and anytime as long as it is connected to the internet. This Bebasan language has the potential to be preserved by creating digital content so that the younger generation can know and be more interested in learning the Bebasan language. The method used is the creation of digital content starting from socializing story ideas, creating scenarios in Bebasan language, determining roles, preparing properties, filming, editing videos, and the validation process before uploading to Youtube. This condition is used to attract the younger generation in Serang Banten to get to know their local language again through digital content broadcast through the online media platform youtube